PEMANFAATAN SERBUK KACA DARI JENIS KACA BENING DENGAN KETEBALAN 3-4 MM SEBAGAI BAHAN TAMBAH DALAM PEMBUATAN BATAKO - Ali Syafi’urroziq; Yosef Cahyo Setianto Purnomo; Lucia Desti Krisnawati (Jurnal Manajemen Teknologi & Teknik Sipil, 2018)
Batako is a building material to replace brick, which is composed of sand, portland cement, and water. This type of research is an experimental study in the form of compressive strength testing with the addition of glass powder. We are planning a mixture of brick making materials with a ratio of 1: 6 cement and sand. Making the test object size and external appearance and testing the absorption capacity using a mortar specimen measuring 5 x 5 x 5 cm. Variations in adding glass powder by reducing the amount of sand starting from 0%, 10%, 15%, 20%, and 25% of the weight of the sand. Testing of the mechanical properties of the brick was carried out at the age of 7, 14, and 28 days for the compressive strength test of the brick, and 28 days for the absorption test of the brick. The compressive strength of the concrete blocks increases with age. From the test, it was concluded that the most optimum mixture was the concrete block with a mixture concentration of 25%, namely 58.00 kg / cm² for the results of the concrete block compressive strength test and 11.19 grams for the brick absorption test.Batako merupakan bahan bangunan pengganti batu bata yang tersusun dari pasir, semen portland dan air. Jenis penelitian ini adalah penelitian eksperimen berupa pengujian kuat tekan dengan penambahan serbuk kaca. Perencanaan campuran bahan penyusun batako dengan perbandingan 1 : 6 semen dan pasir. Pembuatan benda uji ukuran dan tampak luar dan pengujian daya serap menggunakan benda uji mortar ukuran 5 x 5 x 5 cm. Variasi penambahan serbuk kaca dengan mengurangi jumlah pasir mulai dari 0%, 10%, 15%, 20%, dan 25% dari berat pasir. Pengujian sifat mekanik batako dilakukan pada umur 7, 14, dan 28 hari untuk uji kuat tekan batako, dan 28 hari untuk uji penyerapan batako. Kuat tekan batako meningkat seiring dengan bertambahnya umur. Dari pengujian disimpulkan bahwa campuran yang paling optimum adalah batako dengan konsentrasi campuran 25% yaitu 58.00 kg/cm² untuk hasil uji kuat tekan batako dan 11.19 gram untuk uji serapan batako.